Healthcare resource utilization and costs by age and joint location among osteoarthritis patients in a privately insured population. (2nd December 2017) - Wang, Susanne X.; Ganguli, Arijit X.; Bodhani, Amit; Medema, Jeroen K.; Reichmann, William M.; Macaulay, Dendy
Abstract: Aims: To compare healthcare resource utilization and costs between patients aged 18–64 years with osteoarthritis (OA) and matched controls without OA in a privately insured population. Methods: Patients with OA were selected from de-identified US-based employer claims (Q1:1999–Q3:2011). The index date was defined as the first OA diagnosis indicated by ICD-9-CM codes. One year before and after the index date were defined as the baseline and study periods, respectively. A second OA diagnosis during the study period was also required. Patients with OA were matched one-to-one on age, gender, index date, and minimum length of follow-up to controls without OA. Baseline characteristics and study period resource utilization and costs (2016 USD) were compared between cohorts. Results: This study identified 199, 539 patients with OA (knee: 87, 271, hip: 19, 953, hand: 15, 670, spine: 12, 496). The average age was 54 years, and 58% were female. OA patients had higher healthcare resource utilization than matched controls in inpatient, emergency room, and outpatient settings ( p < .001 for all). Further, patients with OA had 4-times the excess total medical costs of their matched controls (14, 521 vs 3, 629; p < .001). Patients with hip OA had the highest medical costs among all joint locations. Outpatient and pharmacy costs were similar among patients with knee, hip, and hand OA, but higher in patients with spine OA. In sub-group analyses, older patients (45–64 years old) had higher costs. Limitations: This sample, obtained using claims data, only includes patients who were actively seeking care for OA and were likely symptomatic. Asymptomatic patients would likely not be captured in this analysis. Conclusions: Patients with OA incur greater healthcare resource utilization and costs than patients without OA, with substantial variation by joint location.